Research on reliability of pulsed electrothermal propulsion system of nanosatellite - V. N. Blinov; V. V. Kositsin; A. I. Lukyanchik; P. V. Stepen; P. S. Yachmenev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In the paper have been discussed nanosetellite propulsion system normalization actual themes, as well their acknowledgement by the testing results. To secure needed survival probability P≥0,995, the propulsion system bottlenecks normalized values are defined. The results of propulsion system fatigue test and reliability evaluation also have been presented. The realized count of propulsion system pulse mode switching is 15700. The actual value testing propulsion system survival probability is P=0,9979. That confirms the ability of nanosatellite propulsion system demanded reliability.